La génesis de la teoría relativista de electrones de Dirac (texto original de Helge Kragh) - Vásquez May (traductor), Juan Manuel (2015)
This is a Spanish version of a very important paper, written by a notable historian of physics, Dr. Helge Kragh, which studies one of the great landmarks in the History of Physics: the Relativistic Quantum Theory of Electrons of P. A. M. Dirac (1902-1984). His study includes sources not used before from the Archive for the History of Quantum Physics, from the Niels Bohr Archive in Copenhagen, and analyzes the development of the Relativistic Quantum Mechanics from 1927 until close before the publication of the February 1928 paper of the English Physicist, in critical perspective of his works and his personal appraisals and from other colleagues and historians of his contributions and inventions, giving new elucidations on his methodology, cultural background and, principally, on the role that plays, in Dirac’s procedures, the relativistic and quantum mechanical principles in working out a theoretical synthesis, concordant with his correlative experimental phenomenology, of the electron theory.